2019
DOI: 10.1016/j.chempr.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering a Reversible Covalent-Bonding Assembly to Optically Detect ee in β-Chiral Primary Alcohols

Abstract: The use of parallel synthesis protocols for asymmetric reaction discovery has increased the need for new methods to rapidly determine enantiomeric excess (ee) values. Most chirality sensing is performed on stereocenters that are a (i.e., proximal) to the target functional group. Herein, we demonstrate a design principle to ''reach out'' to more distant stereocenters. Therefore, we see the design principles established in this work as a step forward in sensing distant point chirality and, eventually, multi-ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, many of them are considered as difficult targets or being impossible for other known sensor assays. The functional groups in ( S )‐2‐methylbutanol and 2‐phenylpropanol are remote from the chiral centers, and it is challenging to achieve chirality transfer with metal complexes [5] . ( S )‐β‐citronellol, ( S )‐β‐citronellal, ( R )‐linalool, L ‐isopulegol, L ‐perillyl alcohol, ( R )‐limonene, and L ‐menthone contain one/two double bonds, and the functional groups are remote from the chiral centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of them are considered as difficult targets or being impossible for other known sensor assays. The functional groups in ( S )‐2‐methylbutanol and 2‐phenylpropanol are remote from the chiral centers, and it is challenging to achieve chirality transfer with metal complexes [5] . ( S )‐β‐citronellol, ( S )‐β‐citronellal, ( R )‐linalool, L ‐isopulegol, L ‐perillyl alcohol, ( R )‐limonene, and L ‐menthone contain one/two double bonds, and the functional groups are remote from the chiral centers.…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, CD signals would not be induced. It would require ingenious designs to go beyond this substrate scope [4–6] . In addition, long reaction times and organic solvents are often needed for these sensors which cannot be easily recovered [7] …”
Section: Introductionmentioning
confidence: 99%
“…However,m any of them are considered as difficult targets or being impossible for other known sensor assays.T he functional groups in (S)-2-methylbutanol and 2-phenylpropanol are remote from the chiral centers,and it is challenging to achieve chirality transfer with metal complexes. [5] (S)-bcitronellol, (S)-b-citronellal, (R)-linalool, L-isopulegol, Lperillyl alcohol, (R)-limonene,and L-menthone contain one/ two double bonds,and the functional groups are remote from the chiral centers.T hese molecules are also difficult targets and their optical chirality sensing was only realized recently with specially-selected late transition metal complexes; [6] (R)limonene and L-menthone were also realized with acyclic cucurbiturils. [9] (S)-2-methylbutyl chloride and propylene carbonate contain inert functional groups and their chiroptical sensing has not been reported.…”
Section: Methodsmentioning
confidence: 99%
“…It would require ingenious designs to go beyond this substrate scope. [4][5][6] In addition, long reaction times and organic solvents are often needed for these sensors which cannot be easily recovered. [7] Host-guest chemistry is an alternative method to expand the substrate scope of CD-based chiroptical sensing.F or example,B iedermann and Nau [8] have reported that the complexes of cucurbit [8]uril with dicationic dyes can be applied in chiroptical sensing of av ariety of biological molecules and drug molecules in water.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually we were able to achieve the unique challenge of sensing more distant stereocenters. 1 However, as I pondered asymmetry, I found myself seeing chirality from a new perspective.…”
mentioning
confidence: 99%